Developmental hypothyroxinaemia and hypothyroidism limit dendritic growth of cerebellar Purkinje cells in rat offspring: involvement of microtubule‐associated protein 2 (MAP2) and stathmin. Issue 4 (June 2014) - Wang, Yuan; Wang, Yi; Dong, Jing; Wei, Wei; Song, Binbin; Min, Hui; Teng, Weiping; Chen, Jie
<x xml:space="preserve">Abstract</x> Aims Iodine is essential for the synthesis of thyroid hormone. Iodine deficiency (ID)‐induced hypothyroxinaemia and hypothyroidism during developmental period contribute to impairments of function in the brain, such as psychomotor and motor alterations. However, the mechanisms are still unclear. Therefore, the present research is to study the effects of developmental hypothyroxinaemia caused by mild ID and developmental hypothyroidism caused by severe ID or methimazole (MMZ) on dendritic growth in filial cerebellar Purkinje cells (PCs) and the underlying mechanisms. Methods A maternal hypothyroxinaemia model was established in Wistar rats using a mild ID diet, and two maternal hypothyroidism models were developed with either severe ID diet or MMZ water. We examined the total dendritic length using immunofluorescence, and Western blot analysis was conducted to investigate the activity of microtubule‐associated protein 2 (MAP2), stathmin and calcium/calmodulin‐dependent protein kinase II (CaMKII). Results Hypothyroxinaemia and hypothyroidism reduced the total dendritic length of cerebellar PCs, decreased MAP2 and its phosphorylation, increased stathmin but reduced its phosphorylation and down‐regulated the activity of CaMKII and its phosphorylation in cerebellar PCs on postnatal day (PN) 7, PN14 and PN21. Conclusion Developmental hypothyroxinaemia induced by mild ID and hypothyroidism induced by severe ID or MMZ limit PCs dendritic growth, which may involve in the disturbance of MAP2 and stathmin in a CaMKII‐dependent manner. It suggests a potential mechanism of motor coordination impairments caused by developmental hypothyroxinaemia and hypothyroidism.